AN INVERSE PROBLEM USING GREEN’S FUNCTIONS AND TFBGF METHOD TO INDENTIFICATE A MOVING HEAT SOURCE IN 3D HEAT CONDUCTION - Ribeiro, S. S.; Oliveira, G. C.; Guimarães, G. (Revista de Engenharia Térmica, 2018)
Moving heat source are present in numerous practical problems in engineering. For example, machining process as the Gas tungsten arc welding (GTAW), laser welding, friction stirwleing process or milding problem. Moving heat source are also present in biological heating as the metabolism or in heat thermal treatment. All these cases, the heat input identification is a complex task and represents an important factor in the process optimization. The aim of this work is to investigate both the temperature field as the heat flux delivered to a piece during a process with moving heat source.